'Wannabe Toxic-Free?' From precautionary consumption to corporeal citizenship. Issue 2 (4th March 2017) - Scott, Dayna Nadine; Haw, Jennie; Lee, Robyn
ABSTRACT: Ecological citizens are increasingly encouraged to adopt 'precautionary consumption' – a set of practices aimed at shielding them from the potential health harms of exposures to everyday toxics. The utility and the effects of precautionary consumption in relation to common chemical exposures are investigated. Precautionary consumption is not only of questionable utility, but is fundamentally misguided as an approach for inspiring antitoxics organizing. The failure of this approach is in part due to its assumption of a naturally bounded, autonomous individual who is able to maintain an impermeable boundary between herself and the environment. Drawing on the work of material feminist theorists, it is argued that Gabrielson and Parady's notion of corporeal citizenship, an approach that places bodies into a complex web of material, ecological relations entangled with the social, offers several strategic advantages for framing resistance strategies.